Clinical study on the reasons for and location of failures of metal-ceramic restorations and survival of repairs - (:unkn) unknown (QUINTESSENCE PUBLISHING CO INC, 2002)
Purpose: A recently introduced technique, the Cojet system, using SiOx (Al2O3 coated with silisic acid), provides ultrafine mechanical retention by sandblasting, as well as a chemicophysical bond between the metal/ceramic and the composite resin. This study determined the reasons for and locations of failures of metal-ceramic restorations and evaluated the survival of the intraoral silica-coating system used for the repair of failed restorations. Materials and Methods: A total of 153 patients possessing 289 fractured crowns were involved in this study; 255 of these fractures were on fixed partial dentures, whereas 34 were on single crowns. The mean observation period was 34.6 months. The materials used for the repair process were ESPE-Sil for silane; Visiogem, Sinfony, and Dentacolor as opaquers; and Pertac II Aplitip, Sinfony, and Charisma as repairing composite resins. Results: The majority of the failures (65%) occurred in the anterior region. Sixty percent of the failures were observed at the labial, 27% at the buccal, 5% at the incisal, and 8% at the occlusal regions. The fractures were mainly in the maxilla (75%), predominantly at the labial surface. The overall cumulative survival rates of the repairs (89%) showed that the first failures happened mostly from 1 week to 3 months after the repair, without any difference between the composite resins. Conclusion: The original failures happened mainly during chewing function or because of accidents, iatrogenic factors, and surgical operations, whereas secondary failures after repair using intraoral silica coating and composite resin were due to trauma, chewing function, or lack of rubber dam application.
Keywords: PORCELAIN; STRENGTHS; SYSTEMS